Cost And Environmental Benefits Of Green Hospitals: A Review - Wardana, Muhammad Dhika Dayu; Setyonugroho, Winny; Pribadi, Firman (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
The process of globalization has ushered in a myriad of effects, both beneficial and detrimental, on humanity and the environment. Sadly, environmental degradation, intricately tied to the healthcare sector, stands as a negative outcome of this global phenomenon. Hospitals, prominent agents in environmental decline, produce significant waste and consume vast energy resources. This study delves into the examination of green hospitals and eco-conscious medical establishments crafted to champion sustainability. By conducting an extensive literature review spanning from 2011 to 2021, the research aims to uncover the financial advantages and ecological ramifications associated with green hospitals. Identifying pivotal factors shaping the adoption of green building principles in healthcare facilities serves as the cornerstone of this investigation. Through this analysis, a deeper understanding of the impetus behind the integration of sustainability practices within healthcare infrastructure is sought, ultimately contributing to informed decision-making and the advancement of environmentally responsible healthcare practices.